145 EUROACTION PLUS: a randomised controlled trial on preventive cardiology programme plus intensive smoking cessation with Varenicline for vascular and high CVD risk smokers and their partners—principal results. (16th May 2012) - Kotseva, K; Jennings, C; De Bacquer, D; Hoes, A; De Velasco, J; Brusaferro, S; Jones, J; Mead, A; Tonstad, S; Wood, D
Abstract : Aim: The aim of the EUROACTION PLUS trial was to determine if the nurse-led preventive cardiology programme in primary care, with an intensive smoking intervention including the optional use of Varenicline, could achieve more effective smoking abstinence among persistent smokers with either established vascular disease, or at high risk of developing cardiovascular disease and to reduce overall cardiovascular risk compared to usual care (UC). Methods: EUROACTION PLUS (EA PLUS) was a randomised controlled intervention trial carried out in general practices across 4 European countries: Italy, The Netherlands, Spain and the UK. Vascular patients and people at high risk of developing cardiovascular disease who were current smokers were individually randomised to receive either a professional smoking cessation intervention, which included the optional use of Varenicline, delivered in the context of the nurse-led EUROACTION preventive cardiology programme, or their usual care. The primary outcome was the proportion of non-smokers (7-day prevalence of non-smoking) validated by breath CO (<10 ppm) in intervention compared to usual care at 16 weeks. The secondary outcomes included the proportions of patients achieving the Joint European Societies lifestyle, risk factor and therapeutic targets for cardiovascular disease prevention. Results: 696 patients were recruited: 350 randomised to EA PLUS and 346 to UC. 85% EA PLUS and 83% UC returned at 16 weeks. For the primary endpoint 51% of patients in the EA PLUS arm were abstinent compared to 19% in UC at 16 weeks; OR 4.52 (95% CI 3.20 to 6.39, p<0.0001). In partners, the 7-day point prevalence of abstinence was significantly higher in EA PLUS (73% vs 37%) compared to UC, OR 4.7 (95% CI 1.9 to 11.5, p<0.001). 52.3% of patients in EA PLUS achieved a Mediterranean diet score ≥9, compared to 37.3% in UC (p<0.001). 16.2% in EA PLUS achieved the physical activity target compared to 7.2% in UC (p=0.002) with a significantly higher proportion achieving the METSmax target (Chester Step test): 37.8% in EA PLUS vs 27.3% in UC (p=0.04). Blood pressure target (<140/90 (130/80 diabetes or vascular disease) was significantly higher in EA PLUS (52% vs 43%; OR 1.47, p=0.03) than UC but there were no differences in lipid or glucose management. Prescribing of cardiopr0tective medication was similar in both arms except for lipid lowering drugs; EA PLUS 53% vs UC (45%, p=0.06); high CVD risk individuals 48% EA PLUS vs 39% UC p=0.04). Conclusion: This European trial has demonstrated that the EUROACTION nurse-led preventive cardiology programme, with an intensive smoking cessation intervention including optional Varenicline, helps more vascular and high risk patients, together with their partners, to stop smoking and better achieve the other European lifestyle and blood pressure targets for cardiovascular disease prevention than usual medical care.